Cardiopulmonary fitness in children with congenital heart diseases versus healthy children. Issue 12 (23rd November 2017) - Amedro, Pascal; Gavotto, Arthur; Guillaumont, Sophie; Bertet, Helena; Vincenti, Marie; De La Villeon, Gregoire; Bredy, Charlène; Acar, Philippe; Ovaert, Caroline; Picot, Marie-Christine; Matecki, Stefan
Abstract : Objective: We aimed to compare the cardiopulmonary fitness of children with congenital heart diseases (CHD) with that of age-adjusted and gender-adjusted controls. We also intended to identify clinical characteristics associated with maximum oxygen uptake (VO2max ) in this population. Methods and results: We included in a cross-sectional multicentre study a total of 798 children (496 CHD and 302 controls) who underwent a complete cardiopulmonary exercise test (CPET). The association of clinical characteristics with VO2max was studied using a multivariate analysis. Mean VO2max in the CHD group and control represented 93%±20% and 107%±17% of predicted values, respectively. VO2max was significantly lower in the CHD group, overall (37.8±0.3vs 42.6±0.4 mL/kg/min, P<0.0001) and for each group (P<0.05). The mean VO2max decline per year was significantly higher in CHD than in the controls overall (−0.84±0.10 vs −0.19±0.14 mL/kg/min/year, P<0.01), for boys (−0.72±0.14vs 0.11±0.19 mL/kg/min/year, P<0.01) and for girls (−1.00±0.13 vs −0.55±0.21 mL/kg/min/year, P=0.05). VO2max was associated with body mass index, ventilatory anaerobic threshold, female gender, restrictive ventilatory disorder, right ventricle systolic hypertension, tricuspid regurgitation, the number of cardiac catheter or surgery procedures, and the presence of a genetic anomaly. Conclusions: Although the magnitude of the difference was not large, VO2max among children with CHD was significantly lower than in normal children. We suggest performing CPET in routine follow-up of these patients. Trial registration number: ClinicalTrials.gov NCT01202916 ; Post-results.